2021
DOI: 10.1002/ajmg.a.62439
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing of child–parent trios with bladder exstrophy: Findings in 26 children

Abstract: Bladder exstrophy (BE) is a rare, lower ventral midline defect with the bladder and part of the urethra exposed. The etiology of BE is unknown but thought to be influenced by genetic variation with more recent studies suggesting a role for rare variants. As such, we conducted paired-end exome sequencing in 26 child/mother/ father trios. Three children had rare (allele frequency ≤ 0.0001 in several public databases) inherited variants in TSPAN4, one with a loss-of-function variant and two with missense variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 94 publications
(116 reference statements)
1
7
0
Order By: Relevance
“…The 16p11.2 deletion syndrome (523 kb) in our study is similar to the duplicated CNV published by Pitsava et al ( 2021 ) which was 733 kb and partly overlapping. At least in individuals carrying 16p11.2 deletions, urogenital malformations are common.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The 16p11.2 deletion syndrome (523 kb) in our study is similar to the duplicated CNV published by Pitsava et al ( 2021 ) which was 733 kb and partly overlapping. At least in individuals carrying 16p11.2 deletions, urogenital malformations are common.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies using CMA have detected novel possibly pathogenic microduplications/ deletions in 9% (10 of 110) and 8% (13 of 169), respectively (Draaken et al, 2013 ; von Lowtzow et al, 2016 ). Recently, data on exome sequencing in trios with BEEC were published reporting three gene variants in the WNT3 gene and in the 22q11‐duplicated region ( LZTR1 and CRKL genes), together with new candidate genes and CNVs (Pitsava et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to describe the frequency of commonly noted manifestations of this condition we reviewed our 37 cases, the 10 additional individuals reported in the literature (Tsai et al, 2022) and the original 14 cases described in 2017 (Jansen et al, 2017) for a total of 61 individuals (Figure 5). Full phenotypic details were not available for all cases, particularly regarding neurodevelopmental outcomes, and certain cases were identified in the context of a broader phenotype‐driven cohort such as autism and developmental delays (Coe et al, 2019) or specific birth defects (bladder exstrophy; Pitsava et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Since this publication in 2017, 10 additional individuals have been published (Kuroda et al, 2019; Li et al, 2020; Martin Fernandez‐Mayoralas et al, 2021; Pitsava et al, 2021; Porrmann et al, 2019; Tsai et al, 2022; Zhou et al, 2020) that both reiterate and expand upon this phenotype with novel features including cleft lip and palate (one case; Porrmann et al, 2019), bladder exstrophy (one case; Pitsava et al, 2021), syndactyly (Tsai et al, 2022), and unilateral renal dysplasia with the diagnosis found on fetal exome (Zhou et al, 2020). In total, 6 of these 10 have been diagnosed by exome sequencing (ES; Li et al, 2020; Pitsava et al, 2021; Tsai et al, 2022; Zhou et al, 2020), one by genome sequencing (Martin Fernandez‐Mayoralas et al, 2021) and three via a ~5000 gene panel (Illumina TruSight One; Kuroda et al, 2019; Porrmann et al, 2019). In order to further elucidate the spectrum of manifestations of this rare neurodevelopmental condition, we now report an additional 34 families with JdVS, highlighting the unique developmental and behavioral phenotype, facial gestalt, and gastrointestinal symptoms through physician reports and family interviews.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, 8 FRGs (CDO1, JUN, MAFG, PRDX6, SCD, SLC2A12, TUBE1, TXNRD1) were used to establish the metastasis of BC (22). Pitsava et al found that TUBE1 suppresses BLCA metastasis by promoting ferroptosis through lipid metabolism (23). High expression of SLC2A12 has been found to be associated with glucose metabolism in ferroptosis, which exacerbates the invasion of BLCA (24).…”
Section: Discussionmentioning
confidence: 99%